2014
DOI: 10.30750/ijpbr.2.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of position of greater palatine foramen in central Indian adult skulls: a consideration for maxillary nerve block

Abstract: To anaesthetize posterior part of soft palate for various surgical procedures, knowledge of the position of the greater palatine foramen (GPF) is very important. Blocking of maxillary division of trigeminal nerve or its branches for local anaesthesia is common practice for maxillofacial surgeries. Objective: this study was aimed to determine the morphology of greater palatine foramen in relation to certain fixed points. Methodology: this study was conducted on 86 dry adult Indian skulls. All the measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…As far as could be ascertained there are no previous reports detailing the shape of the LPF. Multiple openings of LPF were present in the majority (68%) of skulls examined in this study, agreeing with the findings of Berge and Bergman (2001), Jaffar and Hamadah (2003), Jotania et al (2013), but in contrast with Hassanali andMwaniki (1988), D'Souza et al (2012), Piagkou et al (2012) and Anjankar et al (2014) who reported a single LPF opening to be dominant. The mean number of LPFs (2.1) observed in the present study is higher than reported previously.…”
Section: Discussionsupporting
confidence: 92%
“…As far as could be ascertained there are no previous reports detailing the shape of the LPF. Multiple openings of LPF were present in the majority (68%) of skulls examined in this study, agreeing with the findings of Berge and Bergman (2001), Jaffar and Hamadah (2003), Jotania et al (2013), but in contrast with Hassanali andMwaniki (1988), D'Souza et al (2012), Piagkou et al (2012) and Anjankar et al (2014) who reported a single LPF opening to be dominant. The mean number of LPFs (2.1) observed in the present study is higher than reported previously.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers undertaking future studies on GPF in Lebanese adults may explore the possibility of replacing this measurement with another that is commonly utilized in studies on dry skulls: Distance to the incisive fossa. [ 11 18 24 34 35 ] Another source of variability in our study may be the possible inclusion of individuals with incomplete growth. We included all patients with fully erupted molars aged over 18 years, which resulted in the inclusion of three individuals younger than 21, of whom two were males (age 19 and 20 years, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The mean distance of the GPF from the incisive foramen, posterior border of the palate and the mid-palatal suture has been 35.9 mm, 3.4 mm and 15.3 mm respectively. 5 A similar study on 300 human skulls of east Indian origin revealed that the GPF was located 1.5 cm from the palatal midline and 0.19 cm from the posterior border of the hard palate. Further the foraman was located distal or in line with the 3rd molar in 57% of the cases with a mere 9.7% located in proximity to the second molar.…”
Section: Discussionmentioning
confidence: 86%
“…In a study using 86 dry skulls of an Indian population, it has been noted that the GPF was located opposite the 3rd maxillary molar in 73.26% of the skulls. 5 A similar study on a chinese population has revealed that the location of the GPF was commonly seen between the maxillary second and third molars (48%) and lingual to the maxillary third molar (33.5%). 6 With the advent of CBCT assessement of vital anatomic landmarks and structure have become more accurate in living individuals and many studies have shed light on the location, size, orientation and variations of the GPF.…”
Section: Introductionmentioning
confidence: 83%